Resource Book on ICT Integrated Teacher Education - Khan, Aerum (Voices of Teachers and Teacher Educators, 2018)
The Commonwealth Education Media Centre for Asia (CEMCA) is the publisher of the edited resource book on ICT Integrated Teacher Education. Dr. Manas Ranjan Panigrahi of CEMCA is the book’s editor. In order to provide high-quality teaching and learning, the book’s five chapters concentrate on the several facets of the necessity of ICT integration in teacher education. The book’s chapters, as stated by the editor, are meant to help knowledgeable educational leaders, teacher educators, school teachers, and others execute technology plans and integrate ICTs into teaching and learning.